Klonasi Manusia, Teknologi, dan Dehumanisasi - Maharani, Septiana Dwiputri (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
Being one of the institution of culture, science can be understood as human activities to understand themselves and their enviroment. While it enables human to adapt to the world, it also causes human to be greddy for the world. Unable to recognize the limit of human power, science, and techonology is frequently in opposition to religion. Human cloning is a case in point, as this is taken the rights of God away from creating the creature. Human cloning, it will be argued, would be a case ofhuman lost in scientific orientation to be human.